Competitiveness and Policy of Soybean Farming in Jeneponto Regency - Sri Mardiyati; Mohammad Natsir; Syafiuddin (Politeknik Negeri Lampung., 2023)
The demand for local soybean commodities is very low compared to imported soybeans, which affects the decline in soybean planting area, and farmers are also less willing to farm soybeans because they are less profitable. Government policies related to soybean self-sufficiency are widely carried out, but imported soybean commodities still have stronger competitiveness. This study aims to analyze the competitiveness and government policies on soybean farming in Tamalatea District, Jeneponto Regency. This study used a survey method. Data collection techniques are observation and interviews. The sampling technique using purposive sampling is to choose soybean farmers who are more productive in their farming, so that the number of samples obtained is 48 farmers. The data analysis technique is quantitative descriptive analysis with the Policy Matrix Analysis method. The results of this study indicate that soybean farming has strong competitiveness, because it has a Private Cost Ratio value of 0.2077 and a Domestic Resource Cost Ratio of 0.1628, with a private profit of Rp 5,752,342.42 per hectare and social profit of Rp 7,682,461.16 per hectare. The input policy on soybean farming resulted in values including: input transfer (IT) of -184,240.32, transfer factor (TF) of Rp 14,365.87, and nominal protection coeficient input (NPCI) of 0.61104. Meanwhile, the output policy resulted in an output transfer (OT) value of Rp -2,099,993.19 and a nominal protection coefficient input (NPCO) of 0.7824. Input-output policies have values including: effectivity policy coeficient (EPC) of 0.7912, subsidy ratio for producer (SRP) of -0.20001, profitability coeficient (PC) of 0.7488, and net transfer (NT) of -1,930,118.73. Government policies that are protective of tradable inputs have a positive impact on soybean farming, so farmers pay lower prices than they should. Government protection policies against tradable output have not been effective, so soybean farmers get output prices that are lower than the price they should. Government policy on tradable inputs simultaneously has not been effective in protecting soybean farming, so it has not been able to provide incentives for increased production.